INTEGRASI PEMBELAJARAN SEJARAH LOKAL DALAM PEMBELAJARAN SEJARAH DI KELAS XI IPS SEMESTER II SMAN 1 BARABAI - Muhammad Aminuddin (Universitas Lambung Mangkurat, 2014)
Learning history is closely related with the life of humans in the past, at present, and in the future. Basically, history is a continuous dialogue between the past, the present, and the future. The purpose of this study is to integrate teaching and learning local history with national history (moment). The students are expected to know the local heroes who fought not only for their country but also in Hulu Sungai Tengah Regency. Local heroes have the good character which can adapted in students life. To explore the character values, this research used naturalistic method (natural setting), it is also known as qualitative approach. The result of observation and interviews show that the learners understand the character of heroic event of the struggle of people against colonialism. From this research it can be concluded that the cultivation of values of local history is closely related with the values of national history, which is very important to improve patriotism of the learners. Thus the development of the values derived from the view of life and the values found in local residence (region).Keywords: history, local, learning, character